2017
DOI: 10.3346/jkms.2017.32.8.1235
|View full text |Cite
|
Sign up to set email alerts
|

Publication Delay of Korean Medical Journals

Abstract: Publication lag is a determinant to journal efficiency that was not yet studied concerning Korean medical journals. To measure publication lag, we investigated the publication timestamps of 4,762 articles published by 10 Korean medical journals indexed in Scopus database, randomly selected from the KoreaMed Synapse since 2013. The total publication lag was 246.5 (Q1, Q3; 178.0, 347.0) days. The overall acceptance lag was 102.0 (65.0, 149.0) days. The overall lead lag was 123.0 (63.0, 236.0) days. The year of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…An additional five days is necessary to make the article available in PubMed. Both, lead and indexing lags in pharmacy practice journals and in the generic comparison group were smaller than those reported by Lee et al among the Korean medical journals [8]. It seems that these post-acceptance delays are not important for authors when they ask for a more rapid editorial process, because at this point, they have already obtained a communication from the editor about the article's acceptance [26].…”
Section: Plos Onementioning
confidence: 69%
See 1 more Smart Citation
“…An additional five days is necessary to make the article available in PubMed. Both, lead and indexing lags in pharmacy practice journals and in the generic comparison group were smaller than those reported by Lee et al among the Korean medical journals [8]. It seems that these post-acceptance delays are not important for authors when they ask for a more rapid editorial process, because at this point, they have already obtained a communication from the editor about the article's acceptance [26].…”
Section: Plos Onementioning
confidence: 69%
“…The editorial process is a compilation of sequential steps with the final aim of ensuring the quality of the papers published. Fig 1 presents the different steps in the scholarly publication process and provides the names for the delays or lags following Lee et al's terminology [8]. Immediately after receiving a manuscript, editors face the responsibility of using the controversial measure of a "quick and brutal" desk rejection of potentially weak or irrelevant manuscripts [9].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies evaluated the publication process times in different biomedical areas and geographic regions, reporting acceptance lag (i.e., time from submission date to acceptance date) of usually over 100 days. [8][9][10][11][12][13][14] Pharmacy Practice reported a first response time after peer review comments of 92 days (SE=5.7) in 2018. 15 We are happy to announce that Pharmacy Practice first response time for original research articles accepted decreased to 80 days (SE=3.8) in 2019, with an acceptance lag of 124 days (SE=5.0).…”
Section: 7mentioning
confidence: 99%
“…In most of those studies, median intervals from submission to acceptance times were approximately 5 to 6 months. 9,[11][12][13][14][15] A larger analysis by Daniel Himmelstein suggests that intervals from submission to acceptance has been reasonably static over the last 30 years, hovering around 120-140 days, 18 with some variability between journals. The rigorous review expected from high-impact journals could plausibly lead to requests for additional experiments or studies after initial review and before final acceptance of a manuscript, thereby extending the interval from submission to acceptance; however, we did not find any such effects.…”
Section: Some Veterinary Journals Have Long Intervals From Sub-missiomentioning
confidence: 99%
“…However, perceptions exist amongst clinicians 4 , and both authors and journal editors have expressed concerns that publication speed is unreasonably slow, and have proposed potential solutions. 5 -7 Various investigators have examined publication speed of journals within biomedical and other scientific fields [8][9][10][11][12][13][14] Investigators have variously identified or excluded factors as contributing to publication speed, including impact factor, type of study, journal type (open-access vs "reader pays", society-published vs.…”
mentioning
confidence: 99%